Road Network Upgrading and Overland Trade Expansion in Sub-Saharan Africa - Buys, Piet; Deichmann, Uwe; Wheeler, David (2012)
Recent research suggests that poor economic integration and isolation from regional and international markets have contributed significantly to poverty in Sub-Saharan Africa. Poor transport infrastructure and border restrictions are major deterrents to trade expansion which would stimulate economic growth and poverty reduction. Using spatial network analysis techniques and gravity trade model estimations, this paper quantifies the economics of upgrading a primary road network that connects the major urban areas in the region. The results indicate that continental network upgrading is worth serious consideration from an economic perspective. Our simulations suggest that overland trade among Sub-Saharan African countries might expand by about $250 billion over 15 years, with major direct and indirect benefits for the rural poor. Financing the programme would require about $20 billion for initial upgrading and $1 billion annually for maintenance.